Interdisciplinary perspectives on sustainability in higher education: a sustainability competence support model - Annelin, Alice; Boström, Gert-Olof (Frontiers in Sustainability, 2024)
After several decades of work towards elevating sustainability education, many have called for a transformation of the education system to create timely action. Teachers, students, organizational leaders and many other stakeholders have voiced their dissatisfaction with their experience of sustainability education. Some say we can do more to create real action for sustainable futures. We investigate what, how and why lectures across disciplines at universities in different countries work with sustainability education. We conduct interviews and dialogues with teachers across disciplines to uncover interdisciplinary perspectives on sustainability education and how to move forward. The emerging reflections provide insights about transformations in strategies and systems, and how to implement sustainability education. There is also a call for reuniting diverse intrapersonal and values thinking between stakeholders to support transformations in sustainability education. Furthermore, participants imagined the future as a creative space where collaboration across disciplines facilitates a student-centred transdisciplinary experience with real-world practice. This study provides insights into the mindset of teachers across disciplines and countries. A sustainability competence-based support model about the current sustainability education discourse is developed.